Right to Privacy in the Development of Digital Technologies - Rustamovich, Bekov Ikhtiyor; Khoshim ugli, Madiev Fakhriddin; Al-Fatih, Sholahuddin (NAJAHA, 2025)
This article analyzes the legal concept and nature of the right to privacy in the context of rapid digital technology development. The study focuses on how constitutional and legal frameworks regulate privacy rights amid digitalization, with particular attention to Uzbekistan’s legal system. Through comparative legal analysis, the research examines legislation and policy documents from countries with advanced digital infrastructures, such as the United States, European Union member states, and Japan. These jurisdictions offer diverse approaches to safeguarding personal data and privacy in the digital environment, which are used to identify similarities, differences, and best practices that may be adapted in Uzbekistan. The primary objective of this study is to formulate recommendations and legal improvements to strengthen the constitutional and legal foundations for protecting the right to privacy in Uzbekistan. The research tasks include analyzing the conceptual and normative nature of the right to privacy, assessing the constitutional guarantees of personal data protection in digital spaces, and proposing appropriate legal mechanisms for enhancing privacy safeguards. The study’s subject matter encompasses theoretical perspectives, relevant national and international legislation, and scientific-legal interpretations concerning privacy rights in digital contexts. This research highlights the urgent need for a more comprehensive legal framework that reflects the realities of technological progress while preserving individual rights. An original contribution of the study is the formulation of author-defined legal concepts such as “right to freedom and private life” and “personal data,” along with identification of privacy’s core legal traits: non-interference and legal protection. These insights aim to inform both legal theory and practical policy reform in Uzbekistan.